2006
DOI: 10.1016/j.placenta.2005.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Advanced Glycation End Products in Women with Preeclampsia: Possible Involvement of Placental Oxidative and Nitrative Stress

Abstract: Advanced glycation end products (AGEs) are known to cause oxidative damage in various cells by binding with its receptor, RAGE. We measured the serum level of AGEs and examined the AGEs, RAGE, and the other biomarkers of oxidative stress in the placentas from preeclamptic women. Competitive ELISA was carried out to measure the AGEs in serum. Western blotting was performed to analyze AGEs and RAGE in the placenta. Immunohistochemical analyses were performed to examine the localization of AGEs, RAGE, and other b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
3
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 50 publications
4
72
3
1
Order By: Relevance
“…This finding was corroborated in a study by Zhu et al, with further evidence revealing increased levels of HMGB1 and RAGE in the placenta of women with severe PE, especially in the cytoplasmic compartment of trophoblasts (Zhu et al 2015). Additionally, RAGE and TLR4, two receptors with affinity for HMGB1, were found to have higher expression in placentas from pregnancies complicated with PE (Kim et al 2005, Chekir et al 2006. Pro-inflammatory effects of HMGB1 via TLR9 have been suggested to contribute to the pathophysiology of PE (Scharfe-Nugent et al 2012).…”
Section: Hmgb1supporting
confidence: 59%
“…This finding was corroborated in a study by Zhu et al, with further evidence revealing increased levels of HMGB1 and RAGE in the placenta of women with severe PE, especially in the cytoplasmic compartment of trophoblasts (Zhu et al 2015). Additionally, RAGE and TLR4, two receptors with affinity for HMGB1, were found to have higher expression in placentas from pregnancies complicated with PE (Kim et al 2005, Chekir et al 2006. Pro-inflammatory effects of HMGB1 via TLR9 have been suggested to contribute to the pathophysiology of PE (Scharfe-Nugent et al 2012).…”
Section: Hmgb1supporting
confidence: 59%
“…In diabetes, there is evidence both in men and in animal models, whether spontaneously occurring (O'Neill et al 2009) or chemically induced diabetic mice (Shrilatha & Muralidhara 2007a, O'Neill et al 2009) and rats (Shrilatha & Muralidhara 2007b), that the condition is associated with marked increases in oxidative stress and sperm nDNA damage. Hyperglycaemia is known to cause oxidative stress (Wautier & Schmidt 2004, Chekir et al 2006 and to accelerate the accumulation of advanced glycation end products and their receptor RAGE, both of which are capable of generating, promoting and/or amplifying oxidative stress and its detrimental consequences. It is this amplification and extension of the injurious oxidative environment that may be responsible for the damage seen in the previously mentioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…This study also shows that mitochondrial oxidative stress damage in the AGEs group was significantly greater when compared to the group without AGEs. The expression of AGEs in maternal serum and in the placenta of the patients with pre-eclampsia was significantly higher when compared to the expression during normal pregnancy [1]. These observations suggest that AGEs maybe participate in the pathophysiology of pre-eclampsia by increasing oxidative stress damage.…”
Section: Ages and Mitochondrial Oxidative Stressmentioning
confidence: 75%
“…Gueds et al [10] have also shown that the accumulation of AGEs can cause oxidative stress in the placenta and placental vascular dysfunction, and thus lead to pre-eclampsia. Chekir et al [1] found that expression of AGEs in maternal serum and in the placenta of patients with pre-eclampsia was significantly higher when compared to the expression during normal pregnancy, and markers of oxidative stress damage in the placenta were significantly increased. Such results could suggest that high expression of AGEs may have as important a role in the pathophysiology of pre-eclampsia as oxidative stress; although the exact mechanism is still unknown.…”
Section: Biological Activity Of Agesmentioning
confidence: 99%
See 1 more Smart Citation